If the sum of first n terms of an AP is 4n – n2, what is the first term i.e. S1? What is the sum of the first two terms? What is the second term? Similarly, find the 3rd, then 10th, and nth terms.

Solution:   Given, Sn = 4n – n2 Therefore, S1 = 4(1) – (1)2 = 4 – 1 = 3 (Answer) And S2 = 4(2) – (2)2 = 8 –…

Continue Reading If the sum of first n terms of an AP is 4n – n2, what is the first term i.e. S1? What is the sum of the first two terms? What is the second term? Similarly, find the 3rd, then 10th, and nth terms.

Show that a1, a2,…, an form an AP where an is defined as below.an = 9 – 5n. Also, find the sum of the first 15 terms in each case.

Show that a1, a2,…, an form an AP where an is defined as below. (ii) an = 9 - 5n. Also, find the sum of the first 15 terms in…

Continue Reading Show that a1, a2,…, an form an AP where an is defined as below.an = 9 – 5n. Also, find the sum of the first 15 terms in each case.